'Selling Sex in Cape Town: Sex Work and Human Trafficking in a South African City.' By Chandre Gould; 'Sugargirls and Seamen.' By Henry Trotter - van Vuuren, Lauren (Kronos: Southern African Histories, 2017)
The two books under review may be on the same topic, namely prostitution, but they are a study in the vagaries of interpretation. Where one titivates and tantalises with pages of lash-batting descriptions of women enmeshed in the world of prostitution, the other gives bluntly and without varnish a grim statistically-driven vision of sex selling. Where one attempts, apparently, to lather the miserable existences under description in a language of double entendres and racy descriptive passages, the other plods plainly through the painful first-hand accounts of the brutalisation and drug addiction experienced by most women selling sex in Cape Town.